2023
DOI: 10.3390/ijms24119135
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mast-Cell-Derived RANKL in Ovariectomy-Induced Bone Loss in Mice

Abstract: Mast cells may contribute to osteoporosis development, because patients with age-related or post-menopausal osteoporosis exhibit more mast cells in the bone marrow, and mastocytosis patients frequently suffer from osteopenia. We previously showed that mast cells crucially regulated osteoclastogenesis and bone loss in ovariectomized, estrogen-depleted mice in a preclinical model for post-menopausal osteoporosis and found that granular mast cell mediators were responsible for these estrogen-dependent effects. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…MCs were shown to produce the receptor activator of the NF-κB ligand (RANKL), the key factor regulating osteoclast formation. It has also been reported that MC-derived RANKL is not involved in the pathology of post-menopausal osteoporosis [ 19 , 20 ].…”
Section: Mast Cellsmentioning
confidence: 99%
“…MCs were shown to produce the receptor activator of the NF-κB ligand (RANKL), the key factor regulating osteoclast formation. It has also been reported that MC-derived RANKL is not involved in the pathology of post-menopausal osteoporosis [ 19 , 20 ].…”
Section: Mast Cellsmentioning
confidence: 99%